I dream of having a large truck to put everybody inside and spend a month in one village, another month in another, to create a collective culture (2014)
Jaider Esbell, artist of the Macuxi people of Rio Branco in the state of Roraima (Brazil), address the subject of the creative experience in indigenous communities. The collective project “The reinvention of time in the perspective of the grandchildren of Macunaima: Roraima indigenous artists and their world views in traditional and contemporary visual arts” gathered plastic arts, literature, photography, audiovisual, handicrafts, music, dance, culinary, drinks, pottery, weaving, orality and body painting, as a communication that evolved together with our own origin. Four works of the artist are presented.